Cover Feature: (Poly)terephthalates with Efficient Blue Emission in the Solid State (Chem. Asian J. 10/2019). Issue 10 (25th April 2019) - Shimizu, Masaki; Shigitani, Ryosuke; Kinoshita, Takumi; Sakaguchi, Hiroshi
Abstract : Based on the electronic structure of 1, 4‐bis(acceptor)‐2, 5‐bis(donor)benzene, 2, 5‐dialkoxyterephthalates were developed as organic luminophores that exhibited blue fluorescence in solution and in the solid state, such as a thin film of poly(methyl methacrylate) (PMMA) and a powder. Polymerization of the terephthalate with or without terephthaloyl chloride produced brilliantly blue fluorescent polymer films. Furthermore, white emission was demonstrated when a fluorescent yellow 2, 5‐bis(diarylamino)terephthalate was doped into the thin film of the blue luminescent polymer. More information can be found in the Full Paper by Masaki Shimizu et al. onpage 1792 in Issue 10, 2019 (DOI:10.1002/asia.201801619 ).